Portreti ot bălgarskoto Srednovekovie: duchovnici - Nikolova, Bistra (Izdatelstvo Nov čovek, 2020)
The book “Portraits from the Bulgarian Middle Ages: Clergymen” by the specialist in church history of Medieval Bulgaria Assoc. Prof. Dr. Bistra Nikolova, can be considered as a continuation of her monograph “Orthodox Churches in the Bulgarian Middle Ages 9th -14th c.”. It includes names and information about over 200 medieval Bulgarian clergymen, representatives of different spiritual degrees and positions, reflected in the Catalog, and acquaints with the life of the medieval Bulgarian clergymen from the village and town, their educational, economic and spiritual status, duties and relations with the laity. (DE-1a)